Structural productivity and carbon emissions in Algeria: An ARDL Model - Chebab, Sihem (International journal of economic perspectives, 2025)
This study investigates the relationship between Algeria’s productive capacity and environmental sustainability over the period 1990–2023. Using the Autoregressive Distributed Lag (ARDL) bounds testing approach within an Error Correction Model (ECM) framework, the analysis examines how structural changes, captured by the Productive Capacities Index (PCI), influence per capita CO₂ emissions. Control variables include economic growth, population, and energy consumption per capita. Unit root tests confirm a mixed integration order, justifying the ARDL method. The bounds test reveals a long-run cointegration among the variables. While long-run coefficients are statistically insignificant, the short-run results show that increases in PCI and energy use significantly raise CO₂ emissions, while population growth reduces them. The error correction term is negative but not significant, indicating weak adjustment to equilibrium. These results suggest that Algeria’s structural development contributes to rising emissions unless accompanied by cleaner technologies and improved environmental policies. Integrating sustainability into economic transformation is crucial for achieving long-term environmental goals.